Efikasi Kombinasi Klorokuin-Primakuin dan Sulfadoksin Pirimetamin-Primakuin Terhadap Malaria Falsiparum Dan Dampaknya Terhadap Siklus Sporogoni Dl Kecamatan Pituruh Kabupaten Purworejo - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Malaria is still a major problem for human health in several districts in Purworejo. Pituruh is one of endemic area, where the incidence of malaria is still high. Beside of increasing number of cases, another problem is the development of resistance of P. falciparum to chloroquine dan sulfadoxine pyrimethamine (SP). The aim of this study therefore is to evaluate the efficacy of antimalarials as the basic for malaria treatment at Pituruh and the impact of treatment for mosquito sporogonic cycle. The study was an experimental study using completely randomized design. The efficacy test were done in vivo using the protocol from WHO 2001. The study was done in community health centre Pituruh I region during September - December 2001. A total of 95 patients with uncomplicated falciparum malaria were divided into two groups, namely 51 subjects for the combined therapy of chloroquine plus primaquine, 44 subjects for combined therapy of SP plus primaquine. The evaluation of sporogonic cycle was done by membrane feeding and direct feeding for subjects contains gametocytes after treatment. Data analysis was done using SPSS version 9.0 and Epi Info 2000. The result of efficacy test for combined therapy of chloroquine plus primaquine/SP plus primaquine showed 54,9%/88,6% adequate clinical and parasitological failure (ACPR) respectively